2021
DOI: 10.3390/cancers13246259
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Potential Prognostic and Predictive Immunological Biomarkers in Patients with Stage I and Stage III Non-Small Cell Lung Cancer (NSCLC): A Prospective Exploratory Study

Abstract: Radiotherapy (RT) and chemotherapy can induce immune responses, but not much is known regarding treatment-induced immune changes in patients. This exploratory study aimed to identify potential prognostic and predictive immune-related proteins associated with progression-free survival (PFS) in patients with non-small cell lung cancer (NSCLC). In this prospective study, patients with stage I NSCLC treated with stereotactic body radiation therapy (n = 26) and patients with stage III NSCLC treated with concurrent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 78 publications
0
23
0
Order By: Relevance
“…As an immune-related gene, MS4A1 was used to predict the prognosis of LURD patients whose dysregulation in interstitial lymphocytes may contribute to the progression of LURD 41,42 . In addition, a prospective exploratory study in patients with stage III NSCLC has shown that CR2 was identi ed as a positive prognostic biomarker which was highly correlated with PFS of patients 43 . What's more, Baglivo S. etc.…”
Section: Discussionmentioning
confidence: 99%
“…As an immune-related gene, MS4A1 was used to predict the prognosis of LURD patients whose dysregulation in interstitial lymphocytes may contribute to the progression of LURD 41,42 . In addition, a prospective exploratory study in patients with stage III NSCLC has shown that CR2 was identi ed as a positive prognostic biomarker which was highly correlated with PFS of patients 43 . What's more, Baglivo S. etc.…”
Section: Discussionmentioning
confidence: 99%
“…Frailer patients are more prone to develop toxicities during CRT, and we can speculate that their immune system might be more severely impaired by CRT jeopardizing immunotherapy efficacy. 18 Based on the aforementioned trials and biological evidence, fit patients treated with SCRT might derive meaningful survival benefit from adjuvant immunotherapy, although data for patients with PS ¼ 2 are largely lacking. Studies should be carried out in this patients' population, as well.…”
Section: Consolidation Immune Therapy After Concurrent or Sequential Crtmentioning
confidence: 99%
“…The main perk of this approach is to engage with a healthy immune system, not impaired by chemotherapy and radiotherapy, as could be the case in an adjuvant approach. 18 Preclinically, a more robust activation of the immune system translated in more effective immune surveillance against micrometastatic disease. 62 An intact tumor itself might imply more neoantigens for priming the immune system.…”
Section: Induction Immunotherapy Followed By Crtmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, our assay showed that non-small cell lung carcinoma (NSCLC) patients treated with stereotactic body radiation therapy (SBRT) had elevated plasma-induced IFN/ISG response activity after treatment, associating with significantly better PFS. 10 …”
mentioning
confidence: 99%